Solution

(sinθ + cosθ) (sinθ + cosθ)

 = sin\(\theta\)(sinθ + cosθ) (sinθ + cosθ) + cos\(\theta\)(sinθ + cosθ) (sinθ + cosθ)

 = sin2\(\theta\) + sin\(\theta\) × cos\(\theta\) + cos\(\theta\) × sin\(\theta\) + cos2\(\theta\)

 = sin2\(\theta\) + sin\(\theta\) × cos\(\theta\) + cos\(\theta\) × sin\(\theta\) + cos2\(\theta\)

 = sin2\(\theta\) + 2 sin\(\theta\) × cos\(\theta\) + cos2\(\theta\)

Solution

(1- tan\(\theta\)) (1+tan\(\theta\)) (1+tan2\(\theta\)) (1+tan4\(\theta\))

= (1 - tan2\(\theta\))(1 + tan2\(\theta\))(1 + tan4\(\theta\))

= (1 - tan4\(\theta\))(1 + tan4\(\theta\)) 

 1 - tan8\(\theta\)

Solution

\(\frac{1}{1 + cosθ}\) + \(\frac{1}{1-cosθ}\) 

 =  \(\frac{1}{1 + cosθ}\) + \(\frac{1}{1-cosθ}\)   

 = \(\frac{1-cosθ +1+cosθ}{(1-cosθ)(1-cosθ)}\)

 = \(\frac{2}{1-cosθ}\) = \(\frac{2}{sin^2θ}\) =  2 cosec2θ

 Solution

 = \(\frac{1}{secA - tanA}\) - \(\frac{1}{secA + tanA}\)

 = \(\frac{secA + tanA - (secA - tanA)}{sec^2A - tan^2A}\)

 = \(\frac{secA + tanA - secA + tanA}{1}\)

 = 2 tanA

L.H.S = \(\frac{1 - sin\alpha}{cos\alpha}\)

 = \(\frac{1 - sin\alpha}{cos\alpha}\) × \(\frac{1 + sin\alpha}{1 + sin\alpha}\)

 = \(\frac{1 - sin\alpha}{cos\alpha(1 + sin\alpha)}\)

 = \(\frac{cos\alpha}{(1 + sin\alpha)cos\alpha}\)

 = \(\frac{cos\alpha}{1 +sin\alpha}\) = R.H.S

\(\therefore\) LHS = RHS proved.

 

Solution'

L.H.S = \(\frac{secA - tanA + 1}{secA - tanA - 1}\)

 = \(\frac{(secA - tanA) + (sec^2A - tan^2A)}{(secA - tanA) - (sec^2A - tan^2A)}\)

 = \(\frac{(secA - tanA) + (secA + tanA) (secA - tanA)}{(secA - tanA) - (secA + tanA)(secA - tanA)}\)

 = \(\frac{(secA - tanA)(1 + secA + tanA)}{(secA - tanA)(1 - secA - tanA)}\)

 = \(\frac{1 + secA + tanA}{1 - secA - tanA}\) = R.H.S

\(\therefore\) L.H.S = R.H.S proved.

 

 

Solution

Here, \(\frac{1 + 3sin\theta - 4sin^3\theta}{1 - sin\theta}\)

 = \(\frac{1 - sin\theta + 4sin\theta - 4sin^2\theta + 4sin^2\theta - 4sin^3\theta}{1 - sin\theta}\)

 = \(\frac{1 (1 - sin\theta) + 4 sin\theta(1 - sin\theta) + 4 sin^2\theta(1 - sin\theta)}{1 - sin\theta}\)

 = \(\frac{(1 - sin\theta)(1 +4sin\theta + 4sin^2\theta)}{1 - sin\theta}\)

 = (1)2 + 2×1×2sin\)\theta\) + (2sin\(\theta\))2

 = (1 + 2sin\(\theta\))2 = RHS

\(\therefore\) LHS = RHS proved.